Business Strategy Planning for Terra Atma - The Well-Being Center - Bismantara, Bismantara; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2013)
The idea of Terra Atma was born to serve the urban need in Jakarta for relaxation, spirituality, counseling and coaching. We perceived that the need for this will increase in Jakarta. These people have a high need to be heard and to have a clear reflection on their problems. The main point that it tries to convey is to position the company as a center that care in the outer and inner dimension of each customer and to see them as a whole human being. This research use qualitative data through library research. The author also use interviews methods to gain insight from professional counselors and a principal from a HRD Consultant. The two interviews will give a benchmark data for the research. By scanning the external and internal dimension of the industry for Terra Atma, we can see that its main problem is a weak brand image due to the fact that it is still a start-up company. By using a TOWS Matrix formulation analysis, the author seeks to find a proper solution toward the problem. The solution can be achieved by providing service for multiple segments and using technology to create a networking and promotional tools for the company. The author is also using a Model Business Canvas to elaborate some solutions for Terra Atma. In implementing the business strategies, Terra Atma has formulated several action plans to meet the challenges. This include setting up a website for R&D strategies, use promotional mix both online and offline to gather public awareness for marketing strategies, begin its talent management program for the human resource strategy and collaboration with other company for financial strategy. The plan is expected to be implemented in 2 years. Ã‚Â Key Words: Well-being center, Terra Atma, Business Strategy Planning